2014
DOI: 10.1007/s11033-014-3531-9
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing and immune response of Crassostrea gigas tumor necrosis factor receptor-associated factor 3

Abstract: Diverse alternative splicing isoforms play an important role in immune diversity and specificity. Their role in molluscan host-defense is however poorly understood. We characterized two alternative isoforms of tumor necrosis factor receptor-associated factor 3 (TRAF3) in the Pacific oyster, Crassostrea gigas, which were named CgTRAF3-S and CgTRAF3-L. An intron was retained in CgTRAF3-L, introducing a premature termination codon. Comparison and phylogenetic analysis revealed that CgTRAF3 shared a higher identit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 41 publications
2
6
1
Order By: Relevance
“…A similar expression pattern of TRAF3 under bacterial invasion was also reported in Mediterranean mussel (M. galloprovincialis) (Toubiana et al, 2014) and pearl oyster (P. fucata) (Huang et al, 2012). Interestingly, there are two TRAF3 isoforms in C. gigas, which display contrary expression responses to Gram-negative bacterial challenge: CgTRAF3-L is significantly up-regulated, whereas CgTRAF3-S is significantly down-regulated (Huang et al, 2014). No such multiple isoforms of TRAF3 have yet been isolated in other bivalve species.…”
Section: Pytraf3ip1 Expression Was Ubiquitously Detected Insupporting
confidence: 74%
See 1 more Smart Citation
“…A similar expression pattern of TRAF3 under bacterial invasion was also reported in Mediterranean mussel (M. galloprovincialis) (Toubiana et al, 2014) and pearl oyster (P. fucata) (Huang et al, 2012). Interestingly, there are two TRAF3 isoforms in C. gigas, which display contrary expression responses to Gram-negative bacterial challenge: CgTRAF3-L is significantly up-regulated, whereas CgTRAF3-S is significantly down-regulated (Huang et al, 2014). No such multiple isoforms of TRAF3 have yet been isolated in other bivalve species.…”
Section: Pytraf3ip1 Expression Was Ubiquitously Detected Insupporting
confidence: 74%
“…With innate immunity, they have evolved elaborate mechanisms to protect themselves against pathogenic invasion. As an important gene that functions in innate immunity, TRAF3 has been identified and characterized in several marine bivalves, such as Pinctada fucata (Huang et al, 2012), Crassostrea gigas (Huang et al, 2014), Patinopecten yessoensis and Mytilus galloprovincialis (Toubiana et al, 2014). The regulated expression of bivalve TRAF3s in response to bacterial challenge that has been revealed in these studies implies the involvement of TRAF3 and its related molecules in innate immunity of shellfish.…”
Section: Introductionmentioning
confidence: 65%
“…There is also evidence of massive expansion and functional divergence among oyster innate immunity genes 39 . To better understand the function of the oyster RLR signalling pathway, we first cloned a number of key oyster genes homologous to those encoding mammalian RLR antiviral signalling pathway proteins, including CgRIG-I-1 ( Cg24392 , GenBank Accession number: KY630188), CgMAVS (GenBank Accession number: KY630189), CgTRAF2 44 ( Cg08964 ), CgTRAF3 45 ( Cg23158 ), CgTRAF6 ( Cg10206 , GenBank Accession number: KY630190), and two oyster IRF genes, CgIRF2 ( Cg21171 , GenBank Accession number: KY630191) and CgIRF8 ( Cg03270 , GenBank Accession number: KY630192), (see Supplementary data for sequence details) from the genome of C. gigas . Importantly, this includes the first reported cloning of a MAVS gene from an invertebrate.…”
Section: Resultsmentioning
confidence: 99%
“…edulis , MAVS was also found in C . gigas , where its inhibition led to a decrease in TRAF3 expression [ 79 ]. The results of this recent study not only showed that MAVS exists in other oyster species aside from S .…”
Section: Resultsmentioning
confidence: 99%